ANALISIS TERHADAP KEBIJAKAN DEMOSI PADA PEKERJA PT. MEGAH MITRA SUKSES (STUDI KASUS PUTUSAN NOMOR 146/PDT.SUS-PHI/2016/PN.JKT.PST JO PUTUSAN MAHKAMAH AGUNG NOMOR 257K/PDT.SUS-PHI/2017) - Kesuma Melati; Stanislaus Atalim (Jurnal Hukum Adigama, 2019)
Demotion occurs in a company mainly because of its negative influence on the morale of the workers concerned and can affect the achievement and morale of other workers in the company. Decline in the position of authority, facilities, status and even salary is a punishment for workers. Demosi is not given its arrangement in Law number 13 of 2003 concerning Manpower and other laws and regulations related to employment. Thus, this demotion arrangement can be regulated individually in work agreements, company regulations or collective labor agreements.The company does have the right to move workers in other parts but may not violate Human Rights and violate the provisions of Article 32 paragraph 2 of the Manpower Act which stipulates that placing someone who is not because of his expertise is against the law. Workforce placement must also pay attention to expertise, dignity and human rights and legal protection. The problem examined is how legal protection for workers due to demotion policy at PT. Magnificent Success Partner? And Is the legal consideration of the judge in the decision Number 146/Pdt.Sus-PHI/ 2016/PN.JKT.PST Jo Decision of the Supreme Court Number 257K/Pdt.Sus-PHI/2017 in accordance with the Manpower Act?Demotion will continue to occur if there are no strict rules regarding demotion, the government should make a regulation in the Labor Law regarding demotion, so that the rules regarding demotion become clear and do not harm the workers.